Work performance and administrative efficiency of employees of the Regional Management of Labor and Employment Promotion - Moquegua, 2020. - et. al., Gregorio Arroyo Japura, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The study aims to determine the relationship between work performance and administrative efficiency of the collaborators of the Regional Management of Labor and Employment Promotion in Moquegua during the year 2020. The methodology applied was a basic and correlational study, maintaining a non-experimental cross-sectional design. The research population was defined among the employees of the Regional Management of Labor and Employment Promotion, which is geographically located in the Cercado de Moquegua, in Moquegua district, whose sample corresponded to 34 employees, as a census sample, since the total number of employees was considered. The survey technique was used and the instruments applied were a questionnaire on work performance for the first variable and a questionnaire on administrative efficiency for the second variable. The statistical figures that support this research were processed from the conclusions reached through the application of the instruments. Since the Spearman's Rho coefficient showed a relationship value r = 0.793 and a significance value of 0.000, which represents a considerable positive correlation of 79.3% between the variables corresponding to work performance and administrative efficiency, so, the main conclusion obtained indicate that there is a direct relationship between work performance and administrative efficiency of the employees at the Regional Labor and Employment Promotion Office in Moquegua, during the year 2020.